Individu et justice sociale : autour de John Rawls. - Audard, Catherine; Sève, René; Dworkin, Ronald; Höffe, Otfried; Dupuy, Jean-Pierre; Ricoeur, Paul; Vullierme, Jean-Louis; Van Parijs, Philippe; Boudon, Raymond; Ost, François; Rawls, John (Paris : Seuil, 1988)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Rawls, John